Late Pleistocene and Holocene climates as viewed from Verlore Vlei - Parkington, John (Bernard Price Institute for Palaeontological Research, 1980)
Evidence from a number of sites along the lower reaches of the Verlore Vlei and the adjacent coastline is interpreted as reflecting considerable environmental change since about 18 000 B.P. In particular seven points are relevant.
Main article
Keywords: environmental change; Pleistocene; Holocene